Walking on my grave [large type] - Hart, Carolyn G. (Hart, Carolyn G. Death on demand series, 2017)
"Annie Darling's friend and fellow shop owner Ves Roundtree is a very wealthy woman. Her rich brother entrusted her with his estate, and upon her death, his fortune is to be divided. Several cash-strapped islanders are in line to collect life-changing inheritances. The problem is, Ves is very much alive. Ves hosts a dinner for the prospective beneficiaries and feels a chill in the air that has nothing to do with the wintry season. Not long after, she suffers a bad fall that was no accident. Everyone at the table had a motive but not a shred of evidence was left behind. When one of the suspects is found floating in the harbor and Ves disappears, Annie and her husband Max spring into action to catch a calculating killer before greed takes another life"--Page [4] of cover.